The construction of paternity at the birth of a full-term healthy child - Santos, Suzanne da Silva (2021)
This is a descriptive study with a qualitative approach, carried out in the first quarter of 2019, in rooming-in of a public hospital. It aimed to describe the perception of men who experienced the birth of a full-term healthy child, about the process of construction of the paternity. Data collection took place through semi-structured interviews, with subsequent thematic analysis. Eighteen fathers participated, most of whom were between 20 and 40 years old, married or in civil union, with complete or incomplete high school education, monthly income equivalent to one to three minimum wages. Four thematic units were developed: Planning to have a child; Feelings brought by paternity; Fatherhood brings maturity and new responsibilities; and The care of the father to the binomial. Men showed desire to plan, be present and actively participate in the pregnancy, delivery and care for the newborn; there was also decentralization of maternal care and the active inclusion of fathers in their child's care. Fatherhood generated positive feelings, but also anxiety and anguish regarding the new responsibilities of a father, such as educational and financial.